(untitled) (Contemporary Journal of Social Science Review, 2024)
The key objective of this study is to determine the factors affecting financial well-being of proprietors in Shikarpur district of Pakistan. Specifically, this study is subject to explore the effect of profit management, education level, credit risk and natural risk over the financial wellbeing of the sole proprietors practicing in district Shikarpur. To achieve the objectives of this study, we included the data of 370 respondents collected via close ended questioners. The results reveal that, Profit management, education level, credit risk and natural risk significantly affect the financial well-being of proprietors in Shikarpur district of Pakistan. The study recommends that proprietors should maintain their profit management for the reason of being financial stable, they should also participate in various business training to maintain their business very well. It is also suggested that sole proprietors should have a second plan about natural disasters to better survive if there is a mishap.